Telemetric intra-cranial pressure monitoring: clinical and financial considerations. (4th May 2017) - Barber, James M.; Pringle, Catherine J.; Raffalli-Ebezant, Helen; Pathmanaban, Omar; Ramirez, Roberto; Kamaly-Asl, Ian D.
Abstract: Intracranial pressure (ICP) measurement is an important diagnostic tool in Neurosurgery. Until relatively recently, conventional monitoring has required that subjects be admitted to a hospital bed and the device is only able to be left in-situ for limited periods of time. We have evaluated a Telemetric ICP monitoring system that has been proven, by several other groups worldwide, to permit rapid, repeated and prolonged ICP measurement, in multiple environments. In our unit, 4 patients have been implanted to-date, between the ages of 4 and 16, manifesting a wide range of complex neurosurgical conditions. The sensors have been left in-situ for between 460 and 632 days. There have been no clinical complications and the system has been universally well tolerated. Clinical events, costs and patient experience were all assessed prior to and following implantation. Overall, there was a significant reduction in associated admissions (44.3%), imaging requirements (72.5%) and costs (50.0%). Subjective feedback from both the patients (where possible) and their families was overwhelmingly positive, partly due to (a) the system's ease of use, (b) its ability to reduce the number of admissions/tests required and (c) the facility for rapid measurement of ICP that permitted on-the-spot reassurance of concerns. Additionally, the ability to monitor ICP at home and/or whilst ambulant, has provided measurements that were hitherto inaccessible to our team, facilitating all the potential benefits that analysis of such information would provide. Indeed, we have seen the resultant management in each case has been completely altered by the availability of this data, reaffirming that the importance of being able to obtain it should not be underestimated. The combination of both this and the ability to markedly improve patient experience, along with generating significant cost-savings, lead the authors to suggest that the implantation of this system should be strongly considered in selected individuals.